ICRISAT establishes a new tropical crops information service - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
The International Crop Research Institute for the Semi-Arid Tropics (ICRISAT) based in India carries out research into what has been termed the 'hardest end of the research spectrum': rainfed farming in the semi-arid tropics. The objective is to...